2007
DOI: 10.1021/es062657b
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Bioreduction of Uranium (VI) to Submicromolar Levels and Reoxidation by Dissolved Oxygen

Abstract: Groundwater within Area 3 of the U.S. Department of Energy (DOE) Environmental Remediation Sciences Program (ERSP) Field Research Center at Oak Ridge, TN (ORFRC) contains up to 135 microM uranium as U(VI). Through a series of experiments at a pilot scale test facility, we explored the lower limits of groundwater U(VI) that can be achieved by in-situ biostimulation and the effects of dissolved oxygen on immobilized uranium. Weekly 2 day additions of ethanol over a 2-year period stimulated growth of denitrifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 189 publications
(199 citation statements)
references
References 31 publications
10
189
0
Order By: Relevance
“…Additional clean water was injected at well FW024 at 0.7-0.9 l min À1 to minimize entry of ambient groundwater, increase the pH, and remove nitrate. Detailed descriptions are available elsewhere Luo et al, 2006;Wu et al, 2006aWu et al, , 2007, http:// www.esd.ornl.gov/orifrc/). Stimulation of bacterial growth with ethanol began on day 137 (7 January 2004) and ended on day 754 (15 September 2005) (Wu et al, 2006b.…”
Section: Site Description and Biostimulation Testsmentioning
confidence: 99%
“…Additional clean water was injected at well FW024 at 0.7-0.9 l min À1 to minimize entry of ambient groundwater, increase the pH, and remove nitrate. Detailed descriptions are available elsewhere Luo et al, 2006;Wu et al, 2006aWu et al, , 2007, http:// www.esd.ornl.gov/orifrc/). Stimulation of bacterial growth with ethanol began on day 137 (7 January 2004) and ended on day 754 (15 September 2005) (Wu et al, 2006b.…”
Section: Site Description and Biostimulation Testsmentioning
confidence: 99%
“…Third, the shift in community composition and structure by nutrient input could be substrate dependent. A simple substrate, such as the ethanol used for U bioremediation (58,59), could have less effect in driving communities from determinism to stochasticity. Fourth, under natural settings, an ecosystem is always under multiple and continuous perturbations.…”
Section: Consistency Between Experimental Results and Theoretical Prementioning
confidence: 99%
“…Reduction from a valence of six to four can be mediated by a variety of dissimilatory metal-and sulfate-reducing bacteria (DMRB and DSRB) in liquid batch, including strains of the genera Anaeromyxobacter, Geobacter, Shewanella, and Desulfovibrio (1)(2)(3)(4)(5). Soil columns amended with DMRB, denitrifying bacteria, or DSRB have confirmed that reductive immobilization can occur in simplified soil systems (6,7), and analogous field-scale pilot biostimulation studies have successfully immobilized uranium in the subsurface (8,9).…”
Section: Introductionmentioning
confidence: 94%